Pengolahan Tiram Menjadi Kaldu dan Saus Tiram Bagi Pemberdayaan Perempuan di Gampong Jawa Lama Kecamatan Banda Sakti Kota Lhokseumawe - Prama Hartami; Zulpikar Zulpikar; Mahdaliana Mahdaliana; Boy Haqi; Putri Maulida (JPM: Jurnal Pengabdian Masyarakat, 2020)
Lhokseumawe City is one of the coastal areas that has the potential for potential fishery products and is suitable for development. One of the many fishery products found in the coastal areas of the city of Hokseumawe is oysters. Generally, these oyster seekers are women who live around the coastal area of ??the city of Hokseumawe which has become their daily livelihood. The fishery products obtained by the community have not been managed professionally, so that they have not been able to provide maximum benefits to the welfare of the community. Therefore, education and training are needed for the people of Lhokseumawe City, especially women so that they can increase the selling value of these fishery products. This community service activity will increase their knowledge and skills in processing food made from fishery products, namely oysters. Which later the production of this business will have an impact on improving the community's economy, especially women in the Javanese Village of Lhokseumawe City